Inklusi Keuangan Digital Melalui Loyalitas Dalam Membangun Finansial Teknologi - Pristiyono Pristiyono; Pitriyani Pitriyani; Desi Wanda Sari (Owner : Riset dan Jurnal Akuntansi, 2023)
The uneven understanding of digital financial literacy in labuhanbatu regency needs attention to find information on digital financial implementation. So the purpose of this study is to determine the level of knowledge and digital financial literacy on user decisions and their relationship to consumer loyalty in using financial technology services. The population and sample refer to the provisions of maximum likehood estimation (mle) the number of samples in the survey ranged from 100-200 samples, so the sample set was 100 samples. This study uses sampling techniques with nonprobability sampling with convenience sampling. The type of data selected is primary data sourced from data sources that directly provide data online. The scale technique used by the author chose a likert scale and data analysis techniques in solving problems with the smart pls v.4.0 application to predict the model tested in the study. The final conclusion of this study found that the knowledge level variable is the first independent (exogenous) variable that is important in measuring consumer usage and loyalty decisions in using or choosing financial technology. Meanwhile, the digital financial literacy variable is the second independent (exogenous) variable that has no influence in measuring usage decisions and consumer loyalty in using or choosing financial technology.